Lomatogonium cherukurianum sp. nov. (Gentianaceae) from Sikkim Himalaya. (21st December 2016) - Dey, Sentu K.; Maity, D.
Abstract : Populations of an unknown taxon of Lomatogonium A. Braun have been found during floristic surveys in the alpine pasture of north Sikkim, India. Comparison with morphologically similar taxa ( Lomatogonium stapfii (Burkill) Harry Smith and L. longifolium Harry Smith) revealed that the new populations represent a species new to science, which is described as L. cherukurianum . Data on phenology, ecology and distribution of the new species is provided together with illustrations.